Development of the method of structural and parametric synthesis of the Quanton diagnostic and health complex - Ogorodnyk, Igor; Vуsotska Olena; Ternyuk, Mykola; Bilovol Наnna (Eastern-European Journal of Enterprise Technologies, 2019)
The synthesis method based on the use of information invariants is proposed, and structural-parametric synthesis of the Quanton diagnostic and health complex is performed. Structural and parametric optimization of the complex is carried out according to the performance criterion. As information invariants, complete (within the accepted classification) sets of methods to obtain the functional properties of the complex, phase cycles of the life cycle, structures of technical subsystems and methods for controlling the technicalization levels, productivity and energy efficiency of processes are used. The sets of methods to obtain the functional properties of the complex and phase cycles of the life cycle are formed by elementwise complication of the corresponding attributes. The set of structures of technical subsystems corresponding to certain levels of technicalization of functions is determined on the basis of the periodic system of technical elements. Complete sets of possible structural solutions for methods of controlling the productivity and energy efficiency of processes are obtained by the topological product of the sets of types of objects by the types of methods for ensuring the required properties or qualities of objects. For each structurally different variant, the usual object parameterization procedure and the system of dependencies of the deductive parametric optimization problem are applied. The system of dependencies is a specific case of parametric information invariants. The dependencies are specified using the information about the necessary source data and target transformations occurring in the Quanton complex during the interaction of subsystems. The algorithm for finding an extremely effective solution is step-by-step. This algorithm assumes a step-by-step determination of the optimal process performance parameters within the limiting contours and subsequent improvement of energy efficiency and quality. Due to the use of complete sets of process structures, elements and discrete-continuum procedure of search for the optimal solution, the integration of the optimization of technical innovation is achieved.